Dabigatran for catastrophic antiphospholipid syndrome. Issue 7 (October 2019) - Sarrate, Edurne; Olive, Alejandro; Morales-Indiano, Cristian; Santos-Gómez, Mireia; Orna, Elisa; Monreal, Manuel; Sorigue, Marc
Abstract : N/A: Vitamin K antagonists (VKA) remain the treatment of choice for catastrophic antiphosphilipid syndrome (CAPS). However, when VKAs do not work for a specific patient, direct oral anticoagulants (DOAC) may be a valid therapeutic alternative. We present a patient with a psychiatric disorder and CAPS who was noncompliant to VKA and low-molecular-weight heparin. He was started on dabigatran and has remained thrombosis-free for 8 years. Due to CAPS he has developed progressive renal failure but dabigatran levels were within the expected range. In conclusion, this case report provides anecdotic evidence that dabigatran may be of use in patients with high-risk APS in whom VKA are not an option.